Promovendo a Inclusão Feminina na Computação: Cursos de Programação em Python - Costa, Rhara Ianna Barcelos; Trajano, Vanessa; Aguiar, Nina; Moreno, Lorenza Leao Oliveira; Quintela, Bárbara de Melo; Oliveira, Alessandreia Marta de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.243836, 2024)
Female underrepresentation in the technology sector is often due to prejudices and insecurities that discourage women’s participation in this predominantly male field. This extension project seeks to encourage and support women to enter and remain in technological careers. The aim is to promote gender equality through various initiatives. Opportunities are offered to high school girls to develop programming skills with tutoring in Python. An active presence is maintained on social media as well as at technology events to encourage representation, and social events are organized for women undertaking technology related courses. Python mini-courses are also held for undergraduate students. To date, the project has reached more than 500 followers on Instagram and 9 successful get-together events were held. The project supported 3 monitoring classes in Python. A short introductory course to programming in Python was conducted, and participants attended 6 technology events.